Crisis conceptual y económica de la odontología a propósito de la Ley 100 de 1993 - Arias, Arnulfo (Revista Estomatología, 1999)
In last yeais profetionals and patients have been participating in the administrativa and economic changes that affect directly their condiction. This new situation has let us take part to face the concept offered by the nation. In this way, we'll first try to offer a general vision of the problem with the respective implications to finally stop and review our particular situation that, likeall health profetionals have their own characteristics.